2016
DOI: 10.1177/0272684x16647359
|View full text |Cite
|
Sign up to set email alerts
|

Digital Storytelling as a Narrative Health Promotion Process

Abstract: Digital storytelling (DST) engages participants in a group-based process to create and share narrative accounts of life events. The process of individuals telling their own stories has not been well assessed as a mechanism of health behavior change. This study looks at outcomes associated with engaging in the DST process for vulnerable youth. The project focused on the experiences of Puerto Rican Latinas between the ages of 15 to 21. A total of 30 participants enrolled in a 4-day DST workshops, with 29 complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 29 publications
1
45
0
2
Order By: Relevance
“…In our analyses of the broader experience of participation in DST workshops reported elsewhere, findings indicated measurable increases in positive social interaction, hope, and control over the future due to participation in a DST workshop. 22 Further qualitative evaluation showed that DST made positive, health-bearing effects on intervention participants, including enhanced subjectivity and self-efficacy from the story crafting and digital editing process and an increased sense of social support from the group process. Participants described a sense of relief and value-feeling like DST gave them ''something worthwhile to do and be''-and increased empowerment from being ''listened to,'' having the opportunity to make sense of their experiences, and tell their ''own truths'' in the process.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our analyses of the broader experience of participation in DST workshops reported elsewhere, findings indicated measurable increases in positive social interaction, hope, and control over the future due to participation in a DST workshop. 22 Further qualitative evaluation showed that DST made positive, health-bearing effects on intervention participants, including enhanced subjectivity and self-efficacy from the story crafting and digital editing process and an increased sense of social support from the group process. Participants described a sense of relief and value-feeling like DST gave them ''something worthwhile to do and be''-and increased empowerment from being ''listened to,'' having the opportunity to make sense of their experiences, and tell their ''own truths'' in the process.…”
Section: Discussionmentioning
confidence: 98%
“…Research utilizing DST has been used in a variety of contexts and purposes, including analysis of the texts that emerge during the workshop to explore the meaning of the participants' shared lived experiences described as they produce their digital story, observing participants' experiences of writing, sharing, and digitally producing their own story in digital format, as well as examining the experience of participants' responses to each other's stories when viewing their final products. 15,[22][23][24][25][26][27] While many have gone on to apply these stories to health promotion and risk reduction behavior change studies, [12][13][14] in these workshops, the goal is not to take the messages and use them to change behavior of some target audience, but rather to explore the lived experience of those in the workshop. The research goals are to learn more about the sense-making of the participants' experience (and health related behaviors) and examine the experience of storytelling itself for its potential in meaning-making and building resilience in the community that is represented by the workshop participants.…”
Section: Introductionmentioning
confidence: 99%
“…Data from the LTAS project indicate that seeing people similar to themselves succeed or overcome difficulties by way of perseverant effort raised participants' beliefs that they, too, possessed the capability to master comparable activities. Observing other partici-pants sharing their own stories inspired others to do the same (DiFulvio et al, 2016;Gubrium, Fiddian-Green, Lowe, et al, 2016). Participants referenced "push [ing] through" the fear of telling their story for the first time, despite their life experience of "not be[ing] believed .…”
Section: Mediatorsmentioning
confidence: 99%
“…It helps participants to share their stories and ideas. Resulting digital stories are short, first person visual narratives that synthesize digital images, audio recordings of a first person, told story, music, and text to document personal experiences [10]. Digital storytelling combines the past methods of storytelling with the recent advances in technology and carries people through the past, present and future [11].…”
Section: Types Of Platform For Storytellingmentioning
confidence: 99%